EVENT MANAGEMENT OF OLAH BAKAT SISWA AKTIF (OBASTIF) FOR MADRASAH TSANAWIYAH LEVEL AS PROMOTION STRATEGY AT MA MIFTAHUL QULUB POLAGAN, GALIS PAMEKASAN - Achmad Damanhuri,; Wahyudi, Kacung; Soleh, Badrus; Wafi, Abdul (re-JIEM (Research Journal of Islamic Education Management), 2022)
Olah Bakat Siswa Aktif (OBASTIF)—a talent sport event for Madrasah Tsanawiyah level held at MA Miftahul Qulub Polagan Galis Pamekasan as a promotion strategy which in its implementation goes through stages namely planning, implementation and evaluation. The study focuses on (1) How is the planning of OBASTIF (2) How is the implementation of OBASTIF (3) How is the result of promotion through OBASTIF. This research uses a qualitative approach with a descriptive type. The data were obtained through interviews, observation, and documentation. The informant are school principal, teachers, and students of Miftahul Qulub Polagan. The research results show that: First. The planning for the OBASTIF covers: a). determining the purpose of the event, b). defining the forms of the event. c). Arranging the event details, d). forming a work team by involving OSIS (Student Council), e). preparing a budget. Second, the implementation process covers distributing brochures and giving delegation letters which are carried out a week before registration opens which are distributed by OSIS members; registration of the event is at MA Miftahul Qulub Polagan; technical meetings; competitions or events ; closing and giving award. Third, the results obtained by the institution are in accordance with what is expected namely MA Miftahul Qulub Polagan became famous to all schools of promotion target, as the institution which concerns on facilitating students in developing their talents.